Why do People Veto? An Experimental Analysis of the Valuation and the Consequences of Varying Degrees of Veto Power - Werner Güth; Judit Kóvaczs (Center for Economic Studies and ifo Institute (CESifo), 2000)
By vetoing one questions mutually efficient agreements. On the other hand the threat of vetoing may prevent exploitation. Based on a generalization of ultimatum bargaining (Suleiman, 1996) we first elicit the responders' certainty equivalents for three different degrees of veto power. Afterwards the corresponding bargaining rule is implemented. The experimental data reveal that proposers are afraid of more veto power but that responders only care for commanding veto power at all, not for its strength.
Keywords: 330